2020
DOI: 10.3389/fpsyg.2019.03033
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Multi-Partner Mating: A Novel Explanation for Moral Stigma Against Consensual Non-monogamy

Abstract: Life history theory (LHT) predicts that individuals vary in their sexual, reproductive, parental, familial, and social behavior according to the physical and social challenges imposed upon them throughout development. LHT provides a framework for understanding why non-monogamy may be the target of significant moral condemnation: individuals who habitually form multiple romantic or sexual partnerships may pursue riskier, more competitive interpersonal strategies that strain social cooperation. We compared sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 123 publications
0
20
0
2
Order By: Relevance
“…For example, life history theory (Del Giudice et al, 2015) postulates that people with a slower life historymuch like prevention focused people-are oriented toward long term planning and avoid taking risks, whereas those with a faster life history-much like promotion focused peopleare oriented toward immediate gratification and make riskier decisions. Research has shown that people with slower (vs. faster) life history report more short-term and less long-term mating orientations, more germ aversion (but less perceived infectability), and take less health and security risks (Mogilski et al, 2020). In the context of the COVID-19 pandemic, people with a slower (vs. faster) life history also reported more positive attitudes towards precautious behaviors during the pandemic (e.g., wearing a mask in public), and were more willing to donate their plasma to help others with COVID-19 (Corpuz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, life history theory (Del Giudice et al, 2015) postulates that people with a slower life historymuch like prevention focused people-are oriented toward long term planning and avoid taking risks, whereas those with a faster life history-much like promotion focused peopleare oriented toward immediate gratification and make riskier decisions. Research has shown that people with slower (vs. faster) life history report more short-term and less long-term mating orientations, more germ aversion (but less perceived infectability), and take less health and security risks (Mogilski et al, 2020). In the context of the COVID-19 pandemic, people with a slower (vs. faster) life history also reported more positive attitudes towards precautious behaviors during the pandemic (e.g., wearing a mask in public), and were more willing to donate their plasma to help others with COVID-19 (Corpuz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Individual response to a pathogen stress could be also seen through the lens of a life history theory framework (LH), which describes variation in the allocation of finite bioenergetic resources among somatic, mating and parental tasks. Psychological studies evident that the fast life history strategy has been linked to poorer health outcomes and more risker behavior [79]. More active sexual and spatial activities in some males could advocate for the presence of fast LH traits.…”
Section: Discussionmentioning
confidence: 99%
“…While some non-monogamous respondents may have several concurrent sexual partners, this study focused only on two partners if the respondent indicated being non-monogamous. Only half of multi-partner participants of the study by Mogilski et al (2020) reported having two partners, while one quarter had three concurrent partners and one fifth—four or more partners). Studying reasons to engage in sexual activity with each of respondent’s sexual partners (if more than two) may give us a better understanding of reasons to engage in sexual activity with the whole cohort of partners.…”
Section: Limitations and Future Directionsmentioning
confidence: 97%